Factors influencing individual happiness towards quality of life / Wan Aminah Wan Ibrahim and Noor Ayunni Aladin - Wan Ibrahim, Wan Aminah; Aladin, Noor Ayunni (2019)
Quality of life (QOL) is a broad multidimensional concept that usually includes subjective evaluation of both positive and negative aspect of life. Quality of life covers three meanings which are quality of the living environment, quality of performance and subjective enjoyment of life. This chapter highlighted the relationship between factors of individual happiness towards quality oflife. Happiness' is understood as part of latter meaning and it is defined as the overall appreciation of one's life-as-a-whole. The concept of happiness consists of overall evaluation of life which is involves all the criteria figuring in the mind of the individual where it means that how good it feels, how well we meet expectations and how desirable it is deemed to be. Emphirical research shows that there are three factors of individual happiness towrds quality of life which are the occupation, education and income. The analysis illustrates that income is the most influential factors of individual happiness toward quality oflife among residents at Mukim Tasek Gelugor and followed by occupation.